Surface weathering process of earthen heritage under dry-wet cycles: A case study of Suoyang City, China - Qi Zhang; Qingling Guo; Huihui Zhang; Yanwu Wang; Ping Li; Bo Zhang; Chun'an Tang (Journal of Rock Mechanics and Geotechnical Engineering)
Dry-wet cycle is a key factor in surface weathering of earthen heritage, which remains insufficiently explained. It involves the interaction of humidity, stress, and damage. Using the RFPA (realistic failure process analysis) numerical method, this study reproduced the processes of humidity diffusion, deformation, stress, and damage evolution under dry-wet cycles in the soil site of Suoyang City, China. The numerical results indicate that the drying phase following rainfall has the most significant deteriorative impact on the earthen heritage. The evaporation of surface moisture during this phase causes volume shrinkage, which in turn generates tensile stress and leads to the formation of numerous desiccation cracks. Desiccation cracks provide channels for moisture diffusion, which further exacerbates generation of the cracks, leading to a mutual promotion between the two phenomena. Furthermore, during the wetting phase, the model elements undergo hygroscopic expansion, resulting in a slight increase in strain and displacement. Previously formed cracks may exhibit temporary narrowing or closure, but will revert during the subsequent drying phase. Ultimately, the overall displacement increases with the number of dry-wet cycles. The findings provide a theoretical foundation for protection against surface weathering and other damage in earthen heritage in arid regions.